The Impact of Technology-Based Learning on Student Engagement and Achievement in the Digital Era - Bayu Kusumo; Henny sutrisman; Rosmerry Simanjuntak; Adrianus Prihartanto; Askrening Askrening; Reny Yunus (International Journal of Educational Evaluation and Policy Analysis, 2024)
This study aims to analyze the influence of technology-based learning on student engagement and achievement in the digital era. The development of information and communication technology has changed the way of learning and teaching, so that universities are required to adopt new approaches that are more in line with the needs of students in the digital era. This study uses a quantitative method with a survey design to collect data from 200 students involved in the technology-based learning process in various study programs. The instruments used include a questionnaire to measure the level of student engagement and analysis of academic results to assess their achievements. The results of the study indicate that technology-based learning significantly increases student engagement, both in terms of active participation in class and interaction with fellow students and lecturers. In addition, the use of technology in learning also contributes positively to improving student academic achievement. These findings indicate that technology integration in higher education can be an effective strategy to encourage deeper engagement and better achievement among students. This study recommends a broader and more strategic implementation of technology-based learning to improve the quality of education in the digital era.